The Differential Effects of Resveratrol and trans-ε-Viniferin on the GABA-Induced Current in GABAA Receptor Subtypes Expressed in Xenopus Laevis Oocytes - Paul William Groundwater; Kaiser Hamid; Irene Ng; Vikram J. Tallapragada; David E. Hibbs; Jane Hanrahan (Frontiers Media S.A., 2015)
Purpose: The natural products resveratrol and trans-ε-viniferin have been reported to have many beneficial effects, which include the enhancement of cognition and memory. There have been no studies which have reported the effects of these compounds on the different GABAA receptor subtypes and this study aimed to address this. Methods: The effects of both resveratrol, and its dimer, trans-ε-viniferin, have been investigated on different GABAA receptor subtypes expressed in Xenopus laevis oocytes, using the two-electrode voltage clamp technique. Results: Resveratrol induced a current of 22 ± 3.53 nA in the α1β2γ2L subtype of the GABAA receptor (but not in the α5β3γ2L and α2β2γ2L subtypes) when applied alone. It also positively modulated the GABA-induced current (IGABA) in α1β2γ2L receptors, in adose-dependent manner (EC50 58.24 μM). The effects of resveratrol were not sensitive to the benzodiazepine antagonist flumazenil. trans-ε-Viniferin exhibited a different pattern of activity to resveratrol; it alone had no effect on any of the subtypes, but it did negatively modulate the GABA-induced current (IGABA) in all three subtypes. The greatest inhibition was found in the α1β2γ2L subtype (IC50 5.79 μM), with the inhibition in the α2β2γ2L (IC50 of 19.08 μM) and α5β3γ2L (IC50 of 21.05 μM) subtypes being similar. The effects of trans-ε-viniferin in α1β2γ2L and α2β2γ2L receptors werealso not sensitive to the benzodiazepine antagonist flumazenil while, in the α5β3γ2L subtype the effect was not sensitive to the inverse agonist L-655,708, indicating different binding sites for this molecule. Conclusions: The results of the present study indicate that both resveratrol and trans-ε-viniferin modulate the GABA-induced current in different ways, and that trans-ε-viniferin may be a lead compound for the discovery of agents which selectively inhibit the GABA-induced current in α1-containing subtypes. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.